Exploring Prameha Nidana Insights from Acharya Charaka's Perspective - Dhanya. T; Sharma, Shivansh Chandra (International Journal of Contemporary Sciences (IJCS), 2024)
A review article on "prameha nidana" from Acharya Charaka's viewpoint would delve into the ancient Ayurvedic understanding of diabetes mellitus. The doshas and Dushyas are involved in the manifestation of prameha. It would discuss Charaka's classification of prameha into different types based on aetiology, symptoms, and prognosis and the correlation of 20 types to modern terminology. Additionally, it would explore his approach to diagnosis, treatment, prognosis and prevention strategies, which often involve lifestyle modifications, dietary regulations, herbal remedies, and purification therapies like Panchakarma. Charaka's emphasis on holistic health and individualized care will be highlighted throughout the review with special emphasis on vikara vighata bhava abhava prativishesha which plays a major role in the manifestation and non-manifestations of diseases.